The Healing Rate of Type II Odontoid Fractures Treated With Posterior Atlantoaxial Screw-rod Fixation: A Retrospective Review of 77 Patients. Issue 5 (1st March 2019) - Huang, Da-Geng; Zhang, Xin-Liang; Hao, Ding-Jun; He, Bao-Rong; Wang, Xiao-Dong; Liu, Tuan-Jiang
Abstract : Background: In theory, temporary posterior atlantoaxial screw-rod fixation for type II odontoid fractures is a way to preserve rotatory motion. However, the healing rate of type II odontoid fractures treated in this way is unknown; that is, the risk associated with conducting a temporary screw-rod fixation for type II odontoid fractures is unknown. This study investigates the healing rate of type II odontoid fractures treated with posterior atlantoaxial screw-rod fixation by CT imaging and evaluates the feasibility of conducting a temporary screw-rod fixation for type II odontoid fractures. Methods: Patients with type II odontoid fracture who underwent posterior atlantoaxial screw-rod fixation in our spine center from January 2011 to December 2014 were identified. Patients older than 65 years or younger than 18 years were excluded. Those who were confirmed to have healing odontoid fractures on CT imaging were included. Those in whom fracture healing was not confirmed were asked to undergo a CT examination. Fracture healing was confirmed on the basis of the presence of bridging bone across the odontoid fracture site on CT imaging. Results: Seventy-seven patients (56 men and 21 women) were included in the study. The average age of the patients was 40.7 ± 11.6 years (range, 18 to 64 years). The mean duration of follow-up was 26.4 ± 4.6 months (range, 24 to 40 months). Fracture healing was observed in 73 patients (94.8%). Discussion: The healing rate of type II odontoid fractures (with an age range of 18 to 64 years) treated with modern posterior atlantoaxial fixation is relatively high. For patients at that age range, posterior atlantoaxial temporary screw-rod fixation for type II odontoid fractures can be conducted with a low risk of nonunion. Level of Evidence: Level IV, therapeutic